TOKOH ORANG TUA DAN REFLEKSI POLITIK ORDE BARU DALAM NOVEL-NOVEL KARYA KUNTOWIJOYO - Kusmarwanti, Kusmarwanti (LITERA, 2015)
Abstract This study aims to describe the characterization of the elderly, intertextual relations of the characters of the elderly with Ronggowarsito and Nabi Hizdir, and reflection on issues of the New Order politics in Kuntowijoyo’s novels. The data sources were two novels by Kuntowijoyo, namely (a) Mantra Pejinak Ular and (b) Wasripin dan Satinah. The results of the study are as follows. First, the characterization of the elderly is made through two ways, namely the physical and spiritual modes. Second, the character of the elderly in Mantra Pejinak Ular has an intertextual relation with Ronggowarsito and that in Wasripin dan Satinah has an intertextual relation with Nabi Hidzir. Third, the characters of the elderly reflect issues of the New Order politics, including: (a) the image of the ruling party to win in the general election, (b) the loyalty to the ruling party, (c) the arrest and assassination of political opponents, and (d) the economic monopoly and signs of the downfall of the ruler.